Multi-objective control strategy of PV conversion system with storage energy management. Issue 12 (2022) - Traiki, G.; Magri, A. El; Lajouad, R.; Fadili, A. El; Bouattane, O.
Abstract: This paper proposes an advanced control scheme for a hybrid renewable energy system based on a PV conversion system and Li-ion Battery. This strategy ensures three operating modes are handled by a suitable algorithm based specifically on battery State of Charge (SoC): (i) MPPT mode: used when the system is controlled to operate in its Maximum Power point. (ii) CC mode ensures fast battery charging. For this, the current sunk to the battery is controlled to its maximal value. (iii) CV mode: The battery is almost charged, one switch to this mode to preserve the battery by regulating the DC bus voltage to its nominal value. The stability of the nonlinear controller, based on Backstepping and sliding mode, is demonstrated using appropriate Lyapunov functions. Several simulations are used to validate the effectiveness of the controller.